The Principals’ Impact on the Implementation of Inclusion - Thompson, Carmelita (Journal of the American Academy of Special Education Professionals, 2015)
The principal is the key element in shaping and sustaining educational programs that provide children with disabilities the opportunity to be educated in the general education setting. Federal mandates require compliance in educational services for children with disabilities. This has changed the role of principals in education. As schools strive to meet the challenge of implementing the Individuals with Disabilities Education Improvement Act (IDEA) and No Child Left Behind (NCLB) requirements, the principals’ role is essential for the success of these programs. Principals must personally lead the implementation of the inclusion process. Principals must be effective leaders in regard to curriculum, resources, staffing, professional development, and instructional practices. They must be knowledgeable about special education history, laws and policies, and services pertaining to special education. The purpose of the article is to emphasize the importance of the principals’ special education understanding, knowledge, and attitude toward successfully implementing inclusion schools.